Disease Management and the Role of Pharmacists. - Holdford D (Disease Management & Health Outcomes)
Disease management is a new method of managing healthcare which has arisen in response to rising healthcare costs and the integration of healthcare providers. Disease management is defined as an integrated, systems approach to healthcare designed to influence the progression of disease within selected patient populations. In disease management, a detailed analysis of a patient population's medical needs and the resources it consumes is performed in order to design, implement and control the delivery of care. Selection of disease management strategies is based on application of the best scientific evidence currently available. Ideally, disease management crosses organisational and professional boundaries resulting in seamless care for patients. Originating in the managed care literature, disease management has five primary characteristics. The first is a disease focus in which interventions target patient populations which are at risk of or have defined diseases. The second characteristic is the use of a population-based strategy, i.e. one that emphasises the overall care of patient populations rather than of individual patients. The third characteristic of disease management is a systems approach in which the various components of the healthcare system are integrated into a seamless process of care. Fourth, disease management is evidence-based in that it uses information from the medical literature and clinical experience to develop clinical guidelines and protocols for application to clinical practice. Finally, disease management focuses on outcomes rather than processes of care. Pharmacists can fulfil numerous roles in disease management because effective drug therapy is the key to managing most diseases. Pharmacist participation in disease management is often directed toward meeting the needs of managed care organisations (MCOs). Pharmacists will be better able to meet the needs of MCOs if the services they provide are consistent with a population-based, integrated systems approach to healthcare. Pharmacists can accomplish this by working with other pharmacists to provide disease management services for large managed care populations over wide geographical areas and by integrating their services with other healthcare providers. Pharmacists can provide disease management outside of a managed care model by individually submitting claims for disease management services to insurers, by having patients pay for services out-of-pocket and by using disease management as a way of differentiating themselves from competitors. Obstacles to pharmacist participation in disease management include the continued short term, component focus of healthcare insurers, the need for more detailed patient information and outcomes data for pharmacists and the need for more training in disease management for pharmacists.